2022
DOI: 10.3389/fpsyg.2022.996338
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers’ STEM pedagogical content knowledge: A comparative study of teachers in Greece and Turkey

Abstract: This study compares the STEM Pedagogical Content Knowledge of Greek and Turkish preschool teachers. The present research is a comparative descriptive study that aims to determine the STEM Pedagogical Content Knowledge of preschool teachers from Greece and Turkey. A descriptive survey model, a method used in quantitative research, was used as this study’s primary research method. The STEM Pedagogical Content Knowledge Scale (STEMPCK) was used in this study. Six hundred sixty-nine preschool teachers - 104 Greek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…STEM has been pursued internationally since the mid-2000s, while relevant research grew rapidly within the last decade (Irwanto et al, 2022). Researchers highlighted the importance of early exposure to STEM (e.g., Clements et al, 2021;Gozum et al, 2022;Nikolopoulou, 2022a;Wan et al, 2021). Pre-school and first years of primary school provide the basis for future learning in STEM since, for example, science and mathematical skills acquired in early years predict later academic performance (Campbell et al, 2018).…”
Section: Stemmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM has been pursued internationally since the mid-2000s, while relevant research grew rapidly within the last decade (Irwanto et al, 2022). Researchers highlighted the importance of early exposure to STEM (e.g., Clements et al, 2021;Gozum et al, 2022;Nikolopoulou, 2022a;Wan et al, 2021). Pre-school and first years of primary school provide the basis for future learning in STEM since, for example, science and mathematical skills acquired in early years predict later academic performance (Campbell et al, 2018).…”
Section: Stemmentioning
confidence: 99%
“…STEM curricula in the early primary years of education can facilitate children's natural curiosity through appropriate, and playful experiments, as well as inquiry-based learning . The role of the teachers is important since they can provide young children with the opportunities, resources, and support, in order to be engaged in high-quality STEM experiences (Bagiati et al, 2015;Gozum et al, 2022;Li et al, 2021).…”
Section: Literature Review Stem Education In Early Primary Yearsmentioning
confidence: 99%
“…Previous research that provides innovative and creative learning in elementary school learning makes learning fun and children become enthusiastic about learning, as in research conducted by (Barab et al, 2005;Hunter & Botchwey, 2017), who create innovative and creative learning designs that will make learning more fun and will make children more enthusiastic about learning (Lin & Acosta-Tello, 2017;Lloyd, 2009) also trying to make innovative learning, the researcher believes that if all learning is designed creatively and innovatively, it will increase children's abilities and education in Indonesia will be more advanced, because all elementary school children are interested in creative things, according to their age, they still like things that interest them. Some of the researchers above have tried their research on Mathematics (Gözüm, Papadakis & Kalogiannakis, 2022). This time we will create creative and innovative learning designs for Social Studies learning in Elementary Schools, which will later attract students' attention and make students enthusiastic about learning which will promote education to be better.…”
Section: Introductionmentioning
confidence: 99%
“…Similar research was also carried out by (Nikolopoulou et al, 2015;Kaindio et al, 2014;Namat et al, 2020), revealing that many ECTs feel confident when integrating ICT into the teaching process. In addition, Namat et al, 2020, Parette et al, 2010Tondeur et al, 2012;Ali Ahmad, 2020;Sonia et al, 2019;Andrisyah & Asih, 2021;Kim, 2020) some researchers (Namat et al, 2020;Parette et al, 2010;Tondeur et al, 2012;Ali Ahmad, 2020;Sonia et al, 2019;Andrisyah & Asih, 2021;Kim, 2020) reported that ECTs consider that the use of ICT is suitable in ECE, especially in creating various activities to support children's cognitive development (Gözüm et al, 2022).…”
Section: Introductionmentioning
confidence: 99%